Review of The History of American Literature on Film - Szabó, Helga (AMERICANA E-journal of American Studies in Hungary, 2019)
The History of American Literature on Film Leitch, Thomas 2019 ISBN: 9781628923735 New York: Bloomsbury Academic 464 pages